2006
DOI: 10.2355/isijinternational.46.1345
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Precipitation Behavior of Nb, Ti Complex Microalloyed Steel Produced by Compact Strip Processing

Abstract: A comprehensive microstructure analyses were conducted for CSP processed Nb, Ti microalloyed steel, especially focusing on the precipitation behavior of the microalloying elements Nb and Ti. After coiling, the steel exhibits mainly a ferrite microstructure. The average ferrite grain size is 5.3 mm. The ferrite has a transitional morphology from polygonal ferrite to non-polygonal ferrite and is characterized by a moderate dislocation density of 2.47Eϩ10/cm 2 . A high density of Nb, Ti complex star-like or cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 11 publications
0
36
0
1
Order By: Relevance
“…The dislocation densities reported in the literature for different microstructures differ considerably. For ferritic phases, a wide range of dislocation density values have been proposed, from very low dislocation density of 10 12 m −2 [12] to a higher ρ of 2.5 × 10 14 m −2 [13]. In the present study, the microstructures observed after a coiling at 700 • C contain secondary phases (MA microconstituent and pearlite) apart from polygonal ferrite.…”
Section: Dislocation Densitymentioning
confidence: 69%
“…The dislocation densities reported in the literature for different microstructures differ considerably. For ferritic phases, a wide range of dislocation density values have been proposed, from very low dislocation density of 10 12 m −2 [12] to a higher ρ of 2.5 × 10 14 m −2 [13]. In the present study, the microstructures observed after a coiling at 700 • C contain secondary phases (MA microconstituent and pearlite) apart from polygonal ferrite.…”
Section: Dislocation Densitymentioning
confidence: 69%
“…For example, in a steel containing 0.044C-0.25Mo-0.0554Nb-0.014Ti, the ferrite grain refinement, solid solution strengthening, and work hardening together contributed up to 65 pct to the yield stress, and the precipitation and transformation (presence of bainite) strengthening contributed 35 pct. [12] In another example, in a steel containing 0.064C-0.0625Nb-0.0435Ti the grain refinement, solid solution strengthening and work hardening together contributed up to 96 pct to the yield stress, and only 4 pct was the contribution from precipitation strengthening, [13] which could be explained by a lower microalloying element content compared to that in. [12] However, in a steel containing 0.06C-0.08Nb-0.07Ti the grain refinement, solid solution strengthening and work hardening together contributed 67 pct to the yield stress, and the remaining 33 pct was the contribution from precipitation strengthening, [14] which is more than 8 times higher compared to that reported in, [13] although the microalloying element content increased by only 0.044 wt pct.…”
Section: Introductionmentioning
confidence: 99%
“…Fine and abundant Ag3Sn hinders the movement of dislocation and increases creep properties [32]. In order to analyze quantitatively the mechanical strength variation by precipitate, Equations (4) and (5) were used as follows [33]:…”
Section: Discussionmentioning
confidence: 99%